How should children with speech sound disorders be classified? A review and critical evaluation of current classification systems. Issue 1 (9th November 2012) - Waring, R.; Knight, R.
Abstract Background Children with speech sound disorders (SSD) form a heterogeneous group who differ in terms of the severity of their condition, underlying cause, speech errors, involvement of other aspects of the linguistic system and treatment response. To date there is no universal and agreed‐upon classification system. Instead, a number of theoretically differing classification systems have been proposed based on either an aetiological (medical) approach, a descriptive–linguistic approach or a processing approach. Aims To describe and review the supporting evidence, and to provide a critical evaluation of the current childhood SSD classification systems. Methods & Procedures Descriptions of the major specific approaches to classification are reviewed and research papers supporting the reliability and validity of the systems are evaluated. Main Contribution Three specific paediatric SSD classification systems; the aetiologic‐based Speech Disorders Classification System, the descriptive–linguistic Differential Diagnosis system, and the processing‐based Psycholinguistic Framework are identified as potentially useful in classifying children with SSD into homogeneous subgroups. The Differential Diagnosis system has a growing body of empirical support from clinical population studies, across language error pattern studies and treatment efficacy studies. The Speech Disorders Classification System is currently a research tool with eight proposed subgroups. The Psycholinguistic Framework is a potential bridge to linking cause and surface level speech errors. Conclusions & Implications There is a need for a universally agreed‐upon classification system that is useful to clinicians and researchers. The resulting classification system needs to be robust, reliable and valid. A universal classification system would allow for improved tailoring of treatments to subgroups of SSD which may, in turn, lead to improved treatment efficacy.